(untitled) (Journal of International Studies, 2020)
The proliferation of international legal and policy instruments for fisheries governance during this post-LOSC era attests to the urgency and strong political commitment of the global community to improve and strengthen the international management and conservation framework for marine capture fisheries, fuelled in part by their mounting concerns over the pervasive unsustainable use and ineffective management of coastal and offshore fisheries worldwide. This paper aims to trace the historical origin and evolution of modern international fisheries regime, focusing on how the current legal and policy framework for responsible fisheries came into being over the last two decades. A series of chronological events that led to this process is examined, stretching back to the periods from 1980s to 2001. Included in this paper is discussion on one of the important driving factors that led to the development global framework for the sustainable and responsible use and management of marine living resources: the need to address the inherent weaknesses of fisheries regime under the LOSC. Finally, the general background of international conferences, conventions, voluntary instruments that have played pivotal role in the development of responsible fisheries concept applicable to coastal States jurisdiction are presented in the paper by examining their scope of application and structure.